Increasing Use of Junk Food in Nepalese Society - Singh, Daman Bahadur (Journal of Development Review, 2021)
Foods that are high in calories, salt, sugar and fat, but protein, vitamins and minerals are almost zero are considered as junk foods Such foods include pizza, burgers, chowmein, bakery items, fried plain roasted food, and highly used foods with food colors and flavors. The use of such foods has increased tremendously in Nepali society. As a result, at an early age, sugar, blood pressure, heart related diseases, kidney related problems, digestive problems, obesity related problems are appearing in Nepalis. In order to solve the health problems caused by the excessive use of junk food in Nepali society, it has become necessary to implement a clear policy to limit the consumption of junk food atthe national level.